Compulsive buying behavior and self-esteem among K-pop fan undergraduate medical students in Jakarta - Julia Rahadian Tanjung; Heunice Precious; Mariani Santosa (Intelektual Pustaka Media Utama, 2026)
The rising popularity of K-pop has attracted many teenagers and young adults. Fans tend to purchase idol merchandise as a sign of support and affection, which can lead to compulsive buying behavior. Compulsive buying behavior is one of the coping mechanisms for low self-esteem. This study aimed to investigate the relationship between self-esteem and compulsive buying behavior among undergraduate medical students in Jakarta who are fans of K-pop. A cross-sectional study was conducted involving 97 students, aged 18 to 25, from various medical schools in Jakarta who were actively engaged as members of a K-pop fan club. Data were obtained through the Revised Edwards Compulsive Buying Scale (ECBS-R) and the Rosenberg self-esteem Scale questionnaire. Among the 97 respondents, 35.1% with low self-esteem, and 51.6% with compulsive buying behavior. A significant relationship was found between self-esteem and compulsive buying behavior (p = 0.014). In conclusion, low self-esteem is associated with compulsive buying behavior among K-pop fan medical students, particularly females, which may adversely impact their academic performance.